Memory and the Wages of Sin: Displacing Rape in Cervantes and Hardy. - MEDING, TWYLA (Journal for Early Modern Cultural Studies)
This essay shows that in Spanish and French iterations of the early modern force of blood plot, the violence of rape is diffused within the bounds of interior spaces, where memory is constructed and then set aside. In his 1613 novella, La fuerza de la sangre, Cervantes builds the verisimilar story of rape on the framework of artificial memory, a structure superseded by the eventual delights of the marriage bed, shared by erstwhile rapist and victim alike. Such repetition of pleasure produces offspring who joyfully retell their parents' reframed story. Ultimately, the truth of that story is located in room and womb, both places of violence transmuted to sites of pleasure. In his dramatic adaptation of the novella, Alexandre Hardy stages a reenactment of the effects of rape, a source of traumatic memory for both victim and perpetrator. In the French tragicomedy, the Spanish heroine's "stolen jewel" of virginity is transformed into the material wages of the ravisher's sin. He clears his debt to the rape victim through a process of atonement and reimbursement that leads swiftly to negation of the past and obliteration of his crime. The act of forgetting privileges the future, giving free rein to Cupid and his ludic games of love, designated by the blindfold and mask that are also the sartorial accessories to abduction.